Exploratory Research on Sports Facilities Construction in Malaysia - Barghchi, Maassoumeh; Omar, Dasimah; Aman, Mohd Salleh; Kazemian, Sina; Huat, Bujang B.K. (American-Eurasian Network for Scientific Information, Jordan, 2010)
Sports and sports facilities development have improved rapidly over the past years inMalaysia. However, such improvements are inadequate compared to the overall development of sportsat international level. In recent years sport is getting more and more influential and it will continueto grow in importance, even for developing countries. Recent developments have witnessed the useof sports facilities as a force for urban growth. The aim of this research is to examine the relationshipbetween sports facilities and urban development in Malaysia. The study uses the expert opinion of town planners, as key players in decision making, working in the specific government's agencies eitherin Kuala Lumpur or all 13 states, who are responsible for formulating and administrating all nationalpolicies relating to town and country planning. The paper argues that simultaneously with emphasison creating a sports culture among Malaysian, there is a need for a new perspective and a newapproach for sports facilities development in the future. In addition, further investigation on theimpacts of sports facilities might help to improve the effectiveness and contribution of sports facilitiesto urban development.